The Influence of Nutrition Education on Balanced Nutritional Patterns Using Lembar baliks on Mothers Knowledge and Toddlers Eating Patterns - Kharani, Audria; Aulia, Rahmi; Sinaga, Haripin Togap (JURNAL KESMAS DAN GIZI (JKG), 2025)
Background: Toddlerhood is a critical period of child growth and development that requires optimal nutritional intake. Underweight toddlers can be caused by chronically low food intake. Maternal ignorance about nutrition can lead to malnutrition, which in turn causes toddlers to eat poorly. Objective: To determine how maternal knowledge and toddler eating habits are influenced by nutrition education about balanced nutrition using lembar balik media. Methodology: Thirty-three mothers with children aged 24 to 59 months participated in this study, which used a single-group pre-post test design. Education was conducted in two meetings using lembar balik media, with different materials in each meeting. Knowledge data were measured using a questionnaire, and the Food Frequency Questionnaire was used to evaluate eating habits (FFQ). The Dependent T-test was used in data analysis. Results: After education, the average score of mothers' knowledge increased from 51.21 to 69.39 (p = 0.000), according to the study. After instruction, the average score of toddlers' eating patterns increased from 264.33 to 324.36 (p = 0.000). Conclusion: Mothers' knowledge and toddlers' eating habits increased as a result of lembar balik media education about balanced and nutritious eating patterns.